Pelanggaran Desersi Pada Prajurit Militer - Astri Dewi Setyarini; Irwan Triadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
In this discussion, the author refers to what desertion is, and how to regulate and resolve desertions committed by military members. The author uses a normative juridical research method where the researcher uses studies from legal sources such as laws, journal papers and books. Desertion is an act of a military member leaving his duties and responsibilities without official permission or a valid reason. This desertion is resolved through the Military Court and carries out a whole series of trials until finally the member is proven guilty of committing the crime of desertion or not.